An Investigation into Shs3 Physics Students Understanding of Data Comparison of Scientific Measurement in Volta Region - Kumassah, K.E.; Ampiah, J.G.; Adjei, E.J. (International Journal of Research Studies in Educational Technology, 2014)
Serious doubt have been raised in the Physics Chief Examiner’s report of the West African Examination Council of Ghana of both physics-1 (theory) and physics-2 (practical) as to whether science students really understand data comparison of physical quantities.In view of this, the researcher use a mixed designed method to gather data from SHS3 physics students’ on their understanding of data comparison of length and time. A population of 422 SHS3 physics students were sampled and a twelve item questionnaire on distance and time administered in order to find out whether the problem enumerated by the Chief Examiners’ of Physics concerning physics students exist and were either with the set paradigm or the point paradigm concept. Also twenty SHS3 physics were purposively selected and interviewed in order to validate students’ written responses.